2019
DOI: 10.1177/0892705719828789
|View full text |Cite
|
Sign up to set email alerts
|

Thermal postbuckling behavior of CNT-reinforced composite sandwich plate models resting on elastic foundations with tangentially restrained edges and temperature-dependent properties

Abstract: Buckling and postbuckling behaviors of sandwich plates reinforced by single-walled carbon nanotube (CNT), rested on elastic foundations and subjected to uniform temperature rise, are investigated in this article. CNT is embedded into matrix phase through uniform or functionally graded distributions. The properties of constituent materials are assumed to be temperature-dependent, and effective properties of nanocomposite are determined by extended rule of mixture. Two models of sandwich plates with face sheets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 63 publications
0
22
0
Order By: Relevance
“…In addition, in the Eqs. (18), A i (i = 1 ÷ 3) and B j (j = 1, 2) are coefficients to be determined. Introduction of Eqs.…”
Section: Formulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, in the Eqs. (18), A i (i = 1 ÷ 3) and B j (j = 1, 2) are coefficients to be determined. Introduction of Eqs.…”
Section: Formulationsmentioning
confidence: 99%
“…Thermal buckling and postbuckling behaviors of thin and moderately thick FG-CNTRC plates have been treated in works [16,17] using an analytical method. Long and Tung [18,19] investigated thermal postbuckling of two sandwich plate models comprising isotropic and FG-CNTRC layers subjected to uniform temperature rise without and with preexisting axial compression. In these works, the FSDT, Galerkin method and an iteration procedure are utilized.…”
Section: Introductionmentioning
confidence: 99%
“…In aforementioned works [29][30][31][32][33], sandwich plates are constructed from isotropic homogeneous core layer and CNTRC face sheets. Beside this model of CNTRC sandwich plate, another model of sandwich plate with CNTRC core layer and homogeneous face sheets has been suggested in recent works of Long and Tung [34,35]. These works indicated that sandwich plate model with CNTRC core layer and thin homogeneous face sheets can give high efficiency of buckling resistance and postbuckling load carrying capabilities.…”
Section: Introductionmentioning
confidence: 99%
“…The volume fractions of CNTs in face sheets corresponding to uniform distribution (UD) and four different types of functionally graded (FG) distributions named as FG-X,, FG-V and FG-O are given in the works[34,35] and omitted here for the sake of brevity.…”
mentioning
confidence: 99%
“…Post‐buckling behaviors of FG‐CNTRC rectangular plates under compressive loads have been considered in works [18, 19] accounting for elasticity of boundary edges. Nonlinear stability of sandwich plates comprising of FG‐CNTRC layers and subjected to mechanical, thermal and thermomechanical loads has been examined in works [20–23].…”
Section: Introductionmentioning
confidence: 99%